1995
DOI: 10.1007/bf00011322
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of leaf water potential and growth in fertigated carob-trees (Ceratonia siliqua L.)

Abstract: Seasonal variations of leaf water potential and growth in fertigatedcarob-trees (Ceratonia siliqua L.) P.J. C o r r e i a and M . A . M a r t i n s -L o u q~o 1 AIDA, Apartado 302, 8100 LouiS, Portugal 1Departamento de Biologia Vegetal Faculdade de Ci6ncias de Lisboa, Campo Grande, Bloco C2, Piso 4, 1700 Lisboa, Portugal Received 9 August 1994. Accepted in revised form 24 November 1994 Key words: branch length, carob, Ceratonia siliqua, evaporation, fertilization, irrigation, leaf water potential, soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…Nevertheless, the results showed that N fertilizer treatments present a slightly higher leaf N content compared to other treatments (Table 3; Figure 2), which is in accordance with previous studies on carob orchards (Correia and Martins-Loução 1997). Leaf N concentration was already found to be an indicator of seedling productivity (Cruz, MartinsLoução, and Lips 1993) and carob yield (Correia and Martins-Loução 1995). In Quercus, Citrus, and olive trees, crops that are distributed along the same edaphoclimatic conditions, similar increments of leaf N concentrations under water-stress conditions were observed (Carranca, Baeta, and Fragoso 1993;Marín Benlloch, and Fernandéz-Escobar 1995;Sabaté and Gracia 1994).…”
Section: Fertilization Effects On Seasonal Variationssupporting
confidence: 52%
“…Nevertheless, the results showed that N fertilizer treatments present a slightly higher leaf N content compared to other treatments (Table 3; Figure 2), which is in accordance with previous studies on carob orchards (Correia and Martins-Loução 1997). Leaf N concentration was already found to be an indicator of seedling productivity (Cruz, MartinsLoução, and Lips 1993) and carob yield (Correia and Martins-Loução 1995). In Quercus, Citrus, and olive trees, crops that are distributed along the same edaphoclimatic conditions, similar increments of leaf N concentrations under water-stress conditions were observed (Carranca, Baeta, and Fragoso 1993;Marín Benlloch, and Fernandéz-Escobar 1995;Sabaté and Gracia 1994).…”
Section: Fertilization Effects On Seasonal Variationssupporting
confidence: 52%
“…Methods to monitor plant water balance at a diurnal time scale include: (a) leaf or fruit sample collection and water content measurements (Klepper, 1968 ; Acevedo et al, 1979 ); (b) sap flow monitoring (Köstner et al, 1998 ); (c) leaf and stem conductance measurements (García-Orellana et al, 2013 ); (d) leaf and stem water potential, photosynthetic capability and hydraulic conductivity measurements (Andrews et al, 2012 ); (e) branch growth and xylem morphometry measurements (Correia and Martins-Loucao, 1995 ; Correia et al, 2001 ). Most of these are invasive processes that involve sampling and are difficult (but possible) to carry out regularly in intervals of a few hours (Chapotin et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, experiments were conducted with cell walls from developing roots and leaves of the slowly growing Ceratonia siliqua L. (Caesalpiniaceae). This species is a drought tolerant, deeply rooted evergreen, and widespread as a native plant in the Mediterranean Basin (Rhizopoulou & Mitrakos 1990;Mitrakos et al 1991;Correia & Martins-Loucao 1995). Also, it is considered a phylogenetically primitive species and an economically important plant, being a resource for afforestation in semi-arid regions (Catarino 1996), and due to the value of its beans (Ortiz et al 1995;Kalaitzakis & Mitrakos 2000) that have been used as a primary source for alternative products (e.g.…”
Section: Introductionmentioning
confidence: 99%